2008
DOI: 10.1016/j.exger.2008.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in parvalbumin immunoreactivity with aging in the central auditory system of the rat

Abstract: To cite this version:Ladislav Ouda, Rastislav Druga, Josef Syka. Changes in parvalbumin immunoreactivity with aging in the central auditory system of the rat. Experimental Gerontology, Elsevier, 2008, 43 (8)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 57 publications
11
71
1
Order By: Relevance
“…In addition, no clear evidence of inter-strain differences in these changes has been reported, in contrast to the findings in calcium binding proteins that are well known to colocalize in neurons with GABA (Kosaka et al, 1987;Kawaguchi and Kubota, 1998). In this case, a significant strain-specificity in their age-related expression was shown for calretinin and parvalbumin (Zettel et al, 1997;Zettel et al, 2001;Ouda et al, 2008). …”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In addition, no clear evidence of inter-strain differences in these changes has been reported, in contrast to the findings in calcium binding proteins that are well known to colocalize in neurons with GABA (Kosaka et al, 1987;Kawaguchi and Kubota, 1998). In this case, a significant strain-specificity in their age-related expression was shown for calretinin and parvalbumin (Zettel et al, 1997;Zettel et al, 2001;Ouda et al, 2008). …”
Section: Introductioncontrasting
confidence: 47%
“…The observed decreased number of GAD-ir (GAD65 and GAD67) neurons in the IC and AC in the present paper cannot be explained simply by a non-selective neuronal loss because in our previous experiments, we did not find any reduction in the total number of neurons in old Long-Evans and Fischer 344 rats on Nissl-stained sections (Ouda et, al., 2008). This finding is in agreement with the data of other authors, who reported no significant changes accompanying aging in the total number of neurons in the inferior colliculus, hippocampus or cortex in rats (Helfert et al, 1999;Poe et al, 2001;Merrill et al, 2001;Stanley and Shetty, 2004).…”
Section: Discussionmentioning
confidence: 71%
“…In the auditory system PV is expressed in cochlear hair cells [11] and in globular bushy cells' endings in the large calyx of Held on the principal cells in the medial nucleus of the trapezoid body [8]. A large number of PV-immunoreactive neurons are present in all subnuclei of the inferior colliculus, PV-positive neurons are scattered throughout layers II-VI in the auditory cortex and sparse small, oval PV-positive neurons are scattered in both the dorsal and ventral divisions of the medial geniculate body [19]. In the case of the medial geniculate body the distribution of GABA-ergic neurons is highly speciesspecific: the proportion ranges from <1% in the bat and rat to about 25% in the cat and monkey [30].…”
Section: Introductionmentioning
confidence: 98%
“…However, only limited information exists on the role of PV in the auditory system. Several recent studies have reported age-related and region-specific changes in the expression of PV-positive neurons in a variety of mammalian species: an age-related decline of calcium binding protein-positive neurons in the dorsal cochlear nucleus of CBA/CaJ mice [13], a decrease in the percentage of PV-expressing neurons in the superficial layers of the auditory cortex of C57Bl/6 mice [17] or an increase of PV-positive neurons in the inferior colliculus of old Long Evans rats and a pronounced decline in the number of PV-positive neurons in the auditory cortex of aged Fischer 344 rats [19]. The assessment of the function of PV in mice has been facilitated by using genetically modified mice deficient for this protein [23].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Moreover, many animal studies have showed the existence of a central component of presbycusis. 4,5 Recent studies of multiple MR imaging modalities have demonstrated their capabilities of offering reliable imaging markers for recognizing presbycusis. In a structural MR imaging study, the volume and surface area were decreased in the auditory cortex areas of patients with presbycusis compared with young healthy controls.…”
mentioning
confidence: 99%